The cause, features and effects of current policy mix of opposing fiscal and monetary policies - Wei Liu (China Finance and Economic Review, 2014)
Currently, China's expansionary fiscal policy and tight monetary policy have formed an opposing policy mix. This is due to the imbalanced macro-economy, which suffers from the pressures of inflation and slow growth. In response to economic changes, China adjusted its monetary policy as the real economy has a weak demand for money. In its reactions to the financial crisis, China adopted a series of policies different from those implemented in European and American countries. For this mix of opposing fiscal and monetary policies to be effective, three conditions should be met: the adjustment of direction should fit the real imbalanced economic situation, financing and investing mechanisms should be market-based, interest rates and exchange rates should gradually become market-determined.
Keywords: 330; Macro-control; Fiscal policy; Monetary policy; Mix of easing and tight policy